PENGARUH PROMOSI DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN PADA PT. TIGA BENUA - Yanto, Eri; Herman, Hendri (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
In the current era, companies are dealing with high competition, commercial business competition leads companies to strive to always behave and make quick decisions in the face of competition. The high level of competition in the business world, forcing companies to achieve competitive advantage in order to win the hearts of consumers. In achieving this the company is required to fulfill and satisfy the needs of its customers well. This study aims to examine how far the role of Promotion and Brand Image can improve Customer Loyalty at PT Tiga Benua. The number of samples taken was 157 respondents who were all customers of PT Tiga Benua specifically covering the Batam center area. T count value for t count promotion (X1) is 3.302 and t count value for brand image (X2) is 7.473, which means that greater than t table is 1.97549. So the hypothesis that their promotion and image are positive for customer loyalty at PT Tiga Benua. Test F obtained by F count> F table or 92,919> 3.05 or significance level (sig) 0,000 <0.05 resulted in a hypothesis approved promotion and brand image and image contributed 54.7% to customer loyalty at PT Tiga Benua.Â Keywords: brand image; customer loyalty; promotion.